Occult Hepatitis B Virus Infection Among Blood Donors in the Capital City of Addis Ababa, Ethiopia: Implications for Blood Transfusion Safety - Gemechu, Gizachew; Abagez, Woldearegay Erku; Alemayehu, Dawit Hailu; Tesfaye, Abebech; Tadesse, Demewoz; Kinfu, Abiy; Mihret, Adane; Mulu, Andargachew (Frontiers in Gastroenterology, 2022)
Background: Occult Hepatitis B Virus Infection (OBI) remains a potential threat for blood safety in developing country. Even so, there is no data are available on the magnitude of occult hepatitis among blood donors in Ethiopia. Therefore, this study aimed to estimate the magnitude of OBI among blood donors in Ethiopia. Objectives: To determine the magnitude of OBI and associated risk factors among blood donors at National Blood Bank, Addis Ababa, Ethiopia. Methods: A total of 973 HBsAg negative plasma samples were tested for anti-HBc antibody using an ELISA and viral DNA using automate ABBOTT real time PCR. Along with plasma samples, demographic data were retrieved from database with respect to donor’s. Both descriptive and inferential statistics were employed for the analysis of data by SPSS 20. P-value less than (0.05) were considered as statistically significant. Results: Of the total 973 study participants, 445 (45.7%) were females with mean age of 26.5 years. A total of 144 (14.8%) blood samples were anti-HBc antibody reactive. Four (0.41% of all; and 2.8% of anti-HBc positive samples) samples were confirmed to have OBI by DNA detection. The mean viral load among the confirmed OBI samples was 31 IU/ml with +/- 12 SD suggesting true occult hepatitis BV infections. Age was found to be risk factors for anti-core positivity and statically significant at (p=0.0001). Conclusion: About four in 1000 blood donors screened negative with HBsAg had occult HBV infection. This shows that there could be a risk of HBV transmission through blood transfusion in Ethiopia. Therefore, there is a need for further investigation and action to revise blood screening strategy including anti-HBc and HBV nucleic acid testing. Keywords: Occult Hepatitis B infection, Hepatitis B virus, Blood donor